Modeling of the stress-strain state of layered orthotropic plates on elastic foundation - Угрімов, Сергій Вікторович; Toрмосов Юрій Михайлович; Куценко, Віктор Анатолійович; Лебединець, Ігор Володимирович (Eastern-European Journal of Enterprise Technologies, 2014)
The problem of the analysis of the stress-strain state of hinged layered plates on elastic foundation is considered. Bending of the layered plate on the Pasternak foundation at its mechanical loading is investigated. Original two-dimensional discrete-structural generalized theory of multi-layered plates is used to study the orthotropic plate bending. This theory is based on developing the displacement vector components of each layer in the power series along transverse coordinate. It allows to calculate displacement and stress tensor components of each layer with the required accuracy. The possibilities of the proposed approach are demonstrated on the examples of studying the response of layered plates on elastic foundation. The reliability of the results, obtained on its basis is determined through comparison with the data, presented in known scientific publications. The effect of the elastic foundation parameters on the stress-strain state of multi-layer structures is investigated. It was found that with an increase in the number of power series terms, displacement and stress demonstrate good convergence. It is shown that the elastic foundation shear stiffness significantly affects the stress-strain state of the hinged layered plates.